Unveiling Tissue‐Specific RNA Landscapes in Mouse Organs During Fasting and Feeding Using Nanopore Direct RNA Sequencing - Chengfei Jiang; Ping Li; Haiming Cao (Advanced Science)
Abstract Understanding tissue‐specific RNA landscapes is essential for uncovering the functional mechanisms of key organs in mammals. However, current knowledge remains limited, as short‐read RNA sequencing—the predominant method for assessing gene expression—depends on incomplete gene annotations and struggles to resolve the diverse transcripts produced by genes. To address these limitations, an integrative approach combining nanopore direct RNA sequencing (DRS), ATAC‐Seq, and short‐read RNA‐seq is used. This method enabled the analysis of RNA landscapes across major mouse organs under fasting and fed conditions, representing two extremes of the caloric cycle. This study uncovered tens of thousands of novel transcripts and identified hundreds of genes with tissue‐specific expression, revealing additional layers of regulated pathways within each organ that conventional short‐read RNA‐seq cannot resolve. By profiling transcript expression across multiple organs under identical conditions, it is conducted comparative analyses exposing significant differences in transcript isoforms and regulations. Moreover, nanopore DRS revealed dynamic changes in poly(A) tail length and m6A modifications of transcripts, many regulated in a tissue‐specific manner. These changes likely contribute to functional differentiation and metabolic specialization of various organs. Collectively, this findings reveal previously unrecognized layers of gene regulation, offering new insights into the metabolic basis of organ function.